Development and characterisation of lanthanum-based bulk metallic glass (bmg) with localised ductilisation - Mohd Qayyum Akbar, Abdul Halim (2022)
Bulk Metallic Glass (BMG) offers properties superior to the present industrialised metal alloy. The properties exceed crystalline metal in terms of hardness, strength, fatigue, and a higher level of stress-strain relation. In this research, the shear band phenomenon was observed through the compression loading on the La61.4Al15.9Ni11.35Cu11.35 BMG samples. The phenomenon was observed through the scanning electron microscope (SEM) and field emission scanning electron microscope (FESEM). In another part of the research, BMG samples with localised ductilisation areas were created through laser processing. The laser process focused the energy into the heat-affected zone (HAZ) and was chosen as the localised heating method. These samples were then made into functionally graded material (FGM) that were based on lanthanum BMG. One of the essential achievements presented in the current work was the optimum laser processing parameters of the La61.4Al15.9Ni11.35Cu11.35 BMG. In addition, ample amount of characterisation testing towards the La61.4Al15.9Ni11.35Cu11.35 BMG samples for expanding the existing knowledge towards this specific BMG alloy system were presented. This would aid with the advancement of BMG manufacturability as the crystalline ductile area. Other than that, other exciting findings under this work for the La61.4Al15.9Ni11.35Cu11.35 BMG were the fracto-emission phenomenon and the fracture response with its microstructure elements. The disadvantage of BMG is the brittleness inherently gained from its amorphous structure, following the shear band phenomenon, which could cause a premature fracture. The advancement of BMG production technology in recent years using laser processing has added an option to the methods available for BMG creation. In future research, post-metal processing procedures on standard metal alloy, such as riveting, screwing and forging, could be prepared on the BMG localised area. The current restrictions of BMG are the size is as-cast inherent brittleness, which affected the machinability and high-temperature process, which affected the meta-stability of the BMG. The capability to join or machine the BMG part to other crystalline metal or BMG parts would increase the part size, shape and BMG practicality. Localised ductilisation of BMG that produced FGM BMG could be a feasible technique to solve the future BMG manufacturability issue.